(untitled) - Osland, Joyce (Upper Saddle River, N.J., 2001)
Reflecting the state of the art in the practice of experiential learning, Organizational Behavior: An Experiential Approach 8/e is teaching students general psychological principles and applying that knowledge to social and organizational situations. It teaches students to become continuous learners, capable of responding to demands for change and new skills throughout their career.
Keywords: Psychology, Industrial,Organizational behavior,Tâm lý học, công nghiệp,Hành vi tổ chức